Support for terrorism: the role of beliefs in jihad and institutional responses to terrorism - Cherney, Adrian (Terrorism and political violence, 2019)
Passive support for terrorism refers to expressions of sympathy for acts of terrorism and/or the justifications (ideology) used by terrorist groups to legitimise their beliefs and actions. One form of passive support is whether Muslims feel terrorists have valid grievances. Appealing to a sense of grievance is a key way that violent Islamists attempt to recruit fellow Muslims to their cause. Using survey data collected from 800 Muslims living in Australia, this paper examines factors that lead Muslims to believe that terrorists have valid grievances. Factors examined include beliefs in jihad and attitudes towards counterterrorism policing and laws. Other variables included in the analysis are social identity, age, gender, income, religious denomination (Sunni vs. Shia), religious commitment, i.e., Mosque attendance, and recent contact with police. The most significant predictor of passive support for terrorism was found to be particular beliefs in jihad. The perceived legitimacy of counterterrorism laws and trust in police were also important. Implications for countering extremist ideology and generating community cooperation in counterterrorism will be considered.